Inorganic Chemical Composition by X-Ray Fluorescence Spectrometry of the Mineral Waters from the Minas Gerais Water Circuit, Brazil - Sandra Regina Damatto (Brazilian Journal of Radiation Sciences, 2021)
The water parks located in the cities of Cambuquira, Caxambu, Conceição do Rio Verde, Lambari and Marimbeiro are part of the Water Circuit of Minas Gerais and have their mineral waters regularly consumed by the local population and tourists motivated by the medicinal use of these waters, characterized as mineral waters. Therefore, the objective of this work was to determine the inorganic chemical composition of the mineral water from these parks, analysing the elements Ag, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K. Mn, Ni, Pb, Se, Ti, V and Zn using the energy dispersive X-ray fluorescence – EDXRF. Despite the proximity to one another, each park has different chemical elements and concentrations. The elements presenting the highest concentrations were the major elements Ca, Fe, K and Mn. However, among the five water parks studied, the Water Park of Caxambu presented the highest concentrations for all the determined elements.